ROLE OF BRICSIN GLOBAL GOVERNANCE,EMPHASIZING BILATERAL TRADE - Shahzad, Dr. Sajid Mehmood; Khan, Muhammad Rafi (The journal of contemporary issues in business and government, 2021)
Global governance is all about interdependence. It started with economic interdependence even without groupings, alignments, and alliances. Bilateral and multilateral economic processes gave rise to joint frameworks in social and political environments. Together they formed a system where ethics and normative principles can also be introduced to increase commonalities to avoid conflicts. Alliances and organizations are consequential evidence of such common agendas. BRICS (Brazil, Russia, India, China, South Africa) is one such example that promotes shared aims. It also has brought apparent enemies, i.e., China and India, closer to fostering economic and political stability for a better global society. Bilateral and multilateral trade among BRICS members is also an important aspect of this study. It is an important endeavor to understand how BRICS emerged as an important player in the international political system. Both role theory and complex interdependence are applied to develop a clear perspective of how one South American, three Asian, and one African nation can assert socially defined roles to reinforce global governance. However, all these nations can also act individually apart from gaining economic and political reinforcements through interdependence. Each nation in BRICS is individually and significantly impacting regional and transregional levels as vibrant and emerging economies. Other regional and transregional groups must take BRICS seriously as the post-American world may see any/most of these economies evolving as hyperpower(s) to challenge unipolarity.